Small-Scale Flume Investigation of the Performance of Step-Baffle Drainage Channels in Mitigating Debris Flows - Li, Shuai; Chen, Xiaoqing; Chen, Jiangang; Tang, Hui; You, Yong; Chen, Huayong; Zhao, Wanyu; Geng, Xueyu (Frontiers in Earth Science, 2022)
Drainage channels are widely used for discharging debris flows into deposition basins or rivers. However, the current drainage channel designs for guiding rapid debris flows downstream do not account for the variations of the gullies’ gradient and debris flow energy. In this study, we evaluate the performance of different step-baffle geometries (square, triangle, and trapezoid) in regulating debris flows. Specifically, their effects on the flow patterns, sediment transport, energy dissipation, and impact pressure are investigated using flume experiments. Results here show that the square baffles promote highly turbulent flows which in turn result in the highest lift height relative to the triangular and trapezoidal baffles. Maximum sediment interception and highest energy dissipation are obtained using the trapezoidal baffle, whereas the triangular baffle exhibits minimal solid interception and the lowest energy dissipation. Trapezoidal baffles generally experience the greatest impact forces relative to both square and triangular baffles. However, when only the first baffle in the channel is considered, it is the square baffles that experience the largest impact forces. The present work improves the understanding of the effectiveness of step-baffle drainage channels in mitigating debris flows.